If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4y + -5) = 60 Reorder the terms: 3(-5 + 4y) = 60 (-5 * 3 + 4y * 3) = 60 (-15 + 12y) = 60 Solving -15 + 12y = 60 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 12y = 60 + 15 Combine like terms: -15 + 15 = 0 0 + 12y = 60 + 15 12y = 60 + 15 Combine like terms: 60 + 15 = 75 12y = 75 Divide each side by '12'. y = 6.25 Simplifying y = 6.25
| 0.6x^2+0.7x+1=0 | | 4h+2h+3h-9h+3h-2=19 | | 700+.5=737 | | 2x-x+8=7 | | y=ax^2-b | | 3c^2-8c+4=0 | | x^2-8y+6x+25+y^2=0 | | 4=3x-18 | | 66-(7x+6)=7(x+2)+x | | 12x-x^2=12.8 | | 22r+18=32r-24 | | a+4a-21=0 | | x^2+49x-380=0 | | -4v+6v=-16 | | 4x^4+2x^3-39x^2+43x-10=0 | | 6x-8x+10=87-21+10x | | x-(-11)=18 | | -7(2t+3)=-35 | | s*4-46=-2 | | 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 |